ANALISIS KUALITAS PELAYANAN PADA BISNIS APOTEK DI PEKANBARU - Mega Putri; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The research is done in Pharmacy Pekanbaru. Setting of the problem is How Service Are Quality In Business Pharmacy Pekanbaru. The purpose of this reseach is to find out quality service in Pharmacy Pekanbaru. Writter use kualitative deskriptive analysis method and some theories about service quality. Indicator used of this research are Tangibles, Reliability, Responsivness, Assurance and Emphaty as measurement of service quality in business pharmacy Pekanbaru. Data collecting technique is done interview and quisoner. Sampling is done by sampling accidental. The result shows that Quality Service in Bussines Pharmacy Pekanbaru is categorized as good.Keyword : Service Quality, Tangibles, Reliability, Responsivness, Assurance and Emphaty